Modeling Analysis Evaluation Selection and Experimental Investigation of Parabolic Trough Solar Collector System - Bhargva, Mohit (My University, 2012)
The PTSC (Parabolic Trough Solar Collector) technology is very useful as it is used for approximately all solar energy applications such as steam and power generation, water heating, air heating etc. In this thesis work the evaluation, comparison, ranking and optimum selection of a PTSC system from the different alternative designs available in the global market is done with the use of systems approach (MADM-TOPSIS, Graph theory). In MADM approach the maximum number of attributes of the PTSC system are identified in an exhaustive way and classified under different categories. The attributes are identified taking into account all the factors i.e. performance, design, materials, cost, quality etc. that affect the PTSC system and are listed in a tabular form. The attributes are assigned codes (numeric, alphabetic) in the coding scheme with an illustration. The ranking and optimum selection of PTSC is done by the use of a mathematical technique called as TOPSIS, and also by line graph and spider graph representation. In Graph Theoretical approach the structural constituents of the PTSC system are identified along with interactions and bonding between them. Five Different subsystems and their sub subsystems along with the interactions between them are identified and represented by a tree diagram and a digraph respectively. The various matrix models and permanent function models are developed for the complete analysis of the PTSC system. A permanent function forms a numerical index and is a unique representation of a PTSC system. The use of systems approaches for the evaluation, ranking and optimum selection of a PTSC is explained and presented in the proposed work with the help of an illustrated example. Also in the proposed work a PTSC system is fabricated for hot water production. Water is used as a working fluid and is recirculated from the storage tank to the absorber tube with the help of a pump. The main aim in the proposed work is to increase the temperature of water in the storage tank to a maximum value. An experimental analysis is done with the main work concentrates on the absorber tube. The values of useful heat gain, overall thermal efficiency, instantaneous efficiency and hourly thermal efficiency are calculated and their variation with time and solar intensity are represented graphically. Firstly a bare Copper and Aluminium tube with 32.5 mm outside diameter and 31.5 inside diameter are used and compared. Then the performance analysis of copper tube with four glass cover tubes of different outside diameters i.e. 45 mm, 55 mm, 65 mm, and 75 mm as an absorber tube is done in terms of temperature of water in the storage tank, useful heat gain, hourly thermal efficiency and instantaneous efficiency to find the optimum design
Master of Engineering (Thermal Engineering)
Keywords: Solar Collector; Modeling; Graph Theoretic Approach; MADM